The League of Nations Participated in the International Labor Organization - Rani, Anita; Kaur Bhullar, Amandeep (International Journal of Psychosocial Rehabilitation, 2021)
The International Labor Organization grew alongside the League of Nations after the Treaty of Versailles in 1919. It was established to reflect the growing support for social reform in the aftermath of World War I, as well as the notion that any change must be carried out on a global scale. After World War II, the Declaration of Philadelphia was a strong rethinking and extension of the ILO’s basic principles and standards. Following the war, the Declaration foresaw an increase in national freedom as well as the start of large-scale specialized collaboration with the creative community. In 1946, the International Labor Organization (ILO) became the first specific office linked with the newly founded United Nations Organization. On the occasion of its 50th anniversary, it received the Nobel Peace Prize in 1969